ANALISIS PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN TEMATIK GURU SEKOLAH DASAR NEGERI 22 PONTIANAK BARAT - Nurmayanti, Yulis; Sugiyono, Sugiyono; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to describe the scientific approach in the thematic learning of grade 1 teachers in 22 Pontianak Barat Elementary School. The research method used is descriptive with a qualitative form of research. The data source of this research is the teachers and students of class 1 C, amounting to 24 students. Data collection techniques used in this study are observation and documentary. Data analysis using steps data reduction, display and conclusion drawing. The data collection instrument used was an observation sheet in the form of an instructional assessment instrument and a learning implementation assessment instrument. This research was conducted four times. the results obtained are 1) The ability of teachers to plan learning has contained a minimum standard of lesson plans containing learning objectives, learning materials, learning methods, learning resources and evaluation evaluation; 2) The ability of the teacher to carry out the approach scientific in thematic learning has been implemented well this is evidenced by the observation that has been done. From the data obtained it was shown that the application of the scientific approach to thematic learning in class I of 22 Pontianak Barat Elementary School was carried out well.Keywords: Analysis, Scientific Approach, and Thematic Approach